Tunable UV/blue luminescence in rare-earth free glass-ceramic phosphor. Issue 10 (August 2019) - Fuertes, V.; Fernández, J.F.; Enríquez, E.
Abstract: A novel rare-earth (RE) free feldspar glass-ceramic phosphor has been designed by a fast sintering route, following a conventional ceramic process. In this work, it is studied how subtle chemical modifications of structural elements may affect luminescence behaviour in this novel matrix. These cation additions acting as glass network former and as modifiers, 1 wt % of SiO2 and CaCO3 or Na2 CO3, respectively, produce a photoluminescence enhancement up to 200%. Whereas, addition of Al2 O3, a glass network former, decreases the photoluminescence emission. Raman spectroscopy evinces a correlation between photoluminescence emission and the Al, Si disorder at microscopic scale. These findings open a new challenge in order to obtain larger structural disorder to make this RE free glass-ceramic much more powerful for future optical applications, highlighting for security markers or light emitting glasses. This new phosphor might be considered as a more sustainable and low-cost alternative to RE phosphors.